Analisis Pengaruh Massa Beban Terhadap Koefisien Redaman Menggunakan Software Python - Stevi Silahooy; Delpina Nggolaon; Aufa Maulida Fitrianingrum (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2024)
This research aims to determine the effect of load mass on the damping coefficient value. The method used in this research is an experimental method where loads with varying masses of 100gr, 120gr, and 140gr are oscillated into three types of liquid, namely water, our oil, and tropical oil. The analysis is based on damped oscillations using Python software which aims to process the data because with the training model in it it is hoped that it will be able to provide more accurate results. Based on the results of data analysis, the damping coefficients (b) for water, minyak kita oil, and tropical oil are respectively (0.0412, 0.0505, 0.0533), (0.1068, 0.1181, 0.1364), and (0.1035, 0.1299, 0.1436). These results indicate that the greater the mass of the load, the greater the resulting damping coefficient.